KOMPETENSI PEDAGOGIK DAN KEDISIPLINAN KERJA GURU-GURU SD YANG BERSERTIFIKAT PENDIDIK DI KECAMATAN PUNDONG BANTUL - Wartomo, Wartomo (Universitas Ahmad Dahlan, 2014)
This study aims to: (1) determine the extent to which the ability padagogik competence, and (2) labor discipline, for primary teachers in Pundong, Bantul. The entire study population of primary school teachers who already bersertikat educators in Pundong, Bantul, until 2012, of which there are 103 people. The research subject is determined based on the amount that is 25% of the members of the population, ie 30 persons (quota sampling), and determined by the draw of the names of elementary school teachers who received a certificate of education (random sampling). Methods of data collection using the guided interview techniques, to determine the understanding of elementary school teachers to implement pedagogical competence and extent of learning. To get the work discipline of data collection techniques used in the work of the observation of the implementation of primary school teachers. Researchers and research instruments made tested on primary school teachers in the district Bambanglipuro, Bantul many as 12 people. The validity of the instrument using content validity (content validity) and reliability of the instrument using a product moment, corrected Zumun Spearman - Brown. Both proved to be a reliable research instrument (r xy = 0.90)> rtabel (N = 12) for pedagogical instrument, and 0.759> rtabel 5% = 0.576). So the instrument can be used for data collection, because it was proven realibel. Data were analyzed using quantitative methods percentage. The results of the data analysis for variable pedagogic work well (70%), whereas for work discipline variables proved to be very good (83%). Suggested further enhanced awareness of elementary school teachers who are already certified educators, to be grateful for the teachers welfare state, through capacity building pedagogical competence and work discipline, so as to improve the quality of learning and lead to the improvement of education quality.